Problems of the implementation of journalistic competencies by students as future radio broadcasting and television workers during their practical training - Davydik, Alexander S.; Mintsevich, Darya A. (Journal of the Belarusian State University. Journalism, 2024)
The article discusses the problems of practical training of students journalists (future workers of radio broadcasting and television) and negative factors affecting the implementation of professional competencies. By interviewing respondents, difficulties in the application of creative and technical skills, problems of interpersonal communication and generation of ideas, and individual and organisational difficulties that arise during the implementation of the practical training programme are identified. Concrete examples demonstrate the students’ attitude to the internship process, their psychological and communicative unpreparedness, as well as the need to strengthen the educational and educational-methodical complexes during practical training.